The Effect of Goat Biourin Liquid Fertilizer with Banana Hump Decomposer on Chemical Properties Ultisol - Dwi Probowati Sulistiyani; Adipati Napoleon; Agus Hermawan; Sofia Sandi; Chintya Vika Lola (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2022)
Ultisols include soils that have very low nutrients, these contents can quickly soil acidity is high, and poor macro nutrient content. Therefore, researchers are making efforts so that ultisols can increase the availability of soil nutrients. The effort is to fertilize using liquid organic fertilizer goat biourin with banana hump decomposer. Liquid organic fertilizer has many advantages, namely the ease of application to soil and plants, which is all you have to do is apply it. This research was conducted in the Greenhouse of the Department of Soil, Faculty of Agriculture, Sriwijaya University. The purpose of this study was to determine the effect of goat Biourin liquid fertilizer on pH, C/N ratio and N-total in Ultisol and to determine the effect of the best dose of goat Biourin liquid fertilizer on pH, C/N ratio and N-total in Ultisol.The raw material for liquid organic fertilizer from goat biourine is goat urine, while the composted material is banana hump. This study used a completely randomized design with 4 treatments and 3 replications. The treatment consisted of the ratio of biourine to water, namely: A (control), B (1:1), C (1:2), and D (1:3). Parameters observed and measured in the study were C/N Ratio, Total N, and soil pH. Based on the results of the study, it was concluded that the type and dosage of goat Biourin liquid fertilizer could increase soil pH, N-total and C/N ratio.